Retrospective Evaluation and Comparison of All Medicolegal Autopsies Performed Before and After the COVID-19 Pandemic in İzmir - Tunçez, Ferhat Turgut; Yeşiltepe, Gözde; Karabulut, Uğur; Tokdemir, Mehmet (The Bulletin of Legal Medicine, 2023)
Objective: In this study, in the 2 year period before and after the first date of the COVID-19 case in Türkiye (between 11.03.2019-10.03.2020 11.03.2020-10.03.2021) İzmir Forensic Medicine Group Presidency we aimed to show the effects of the SARS-CoV-2 pandemic by examining the autopsies and autopsy findings performed through the forensic autopsy records. Methods: Our study was planned as a retrospective study of autopsies performed in İzmir Forensic Medicine Group Presidency. The data of autopsies performed between 11.03.2019-10.03.2020 and 11.03.2020-10.03.2021 in the İzmir Forensic Medicine Group Presidency will be analyzed in terms of age, gender, cause of death, origin of death and mode of death. Results:A total of 4604 autopsy cases were examined in our study. In the pre-pandemic period, the number of female cases was 472 (21.4%), the number of male cases was 1734 (78.6%), the most common form of death was suspicious death with 1192 (54%), and the most common origin was 1039 (47.1%) was detected as natural death. After the pandemic, these numbers were found to be 413 (17.2%) for women, 1985 (82.8%) for men, 1398 (58.3) suspicious deaths and 1072 (44.7%) natural deaths. Conclusion: As in all areas of life, changes have occurred in forensic autopsy practice with the COVID-19 pandemic, and we think it is important to share the data we have obtained as a result of examining and analyzing all forensic autopsies performed during and before the SARS-CoV-2 pandemic in Izmir for two years.